Pemodelan Antarmuka Pengguna Aplikasi Video Online dengan Pertimbangan Pengguna Lansia - Ulfi Muzayyanah Fadil; Kalfida Eka Wati Siregar; Alfira Syah Kadri; M. Khalil Gibran (International Forum of Researchers and Lecturers, 2025)
An online video application specifically designed for the elderly, with a focus on ease of use and fulfillment of entertainment and hobby needs. Common problems of the elderly related to cognitive decline, loneliness, and difficulty adapting to technology are the background to the design of this application. The research method used is the Software Development Life Cycle (SDLC) with a prototyping model. The design process includes creating a process flow diagram, Entity Relationship Diagram (ERD) for database modeling, and an intuitive user interface (UI) design. The results of this study are in the form of an application prototype that includes a login feature (with a no-registration option for the elderly), a homepage with favorite video categories, an interactive search feature, a search results page, and a video player interface with simple interaction options such as like. The interface design prioritizes minimalist aesthetics and navigation that is easy for the elderly to understand. It is hoped that this application can provide alternative entertainment, reduce loneliness, and improve knowledge and decision-making for the elderly through relevant video content.